Dimitrie Cantemir – a personality of European level - Eșanu, Andrei; Eșanu, Valentina (Balcanica Posnaniensia. Acta et studia, 2009)
The article by Andrei and Valentina Eșanu “Dimitrie Cantemir – A Personality of European Level” is devoted to a comprehensive study of the life and multifaceted scholarly legacy of the outstanding Moldavian ruler and scholar Dimitrie Cantemir (1673–1723). The work examines the evolution of his intellectual and cultural formation within the broader context of late 17th–early 18th century Europe, a period when Central and Southeastern Europe were under Ottoman domination. The aim of the study is to present Cantemir as a universal personality who bridged Eastern and Western European cultural traditions and became a forerunner of the Enlightenment in Romanian and European scholarship. The authors analyze the main stages of his biography, the sources of his education, and the wide range of his scientific interests—from philosophy and theology to music, literature, history, and geography. The methodological basis of the article relies on historical-comparative and source-critical approaches, including the analysis of Cantemir’s published and manuscript works (Divanul, Istoria ieroglifică, Descriptio Moldaviae, Incrementorum et decrementorum aulae Othmannicae, and others), as well as the study of influences from ancient, Byzantine, Western European, and Eastern authors whom he cited. As a result, the authors demonstrate that Dimitrie Cantemir was among the first Eastern European scholars to integrate Christian and Muslim cultural traditions within a unified intellectual framework. His works laid the foundations of Romanian historical, philosophical, and musical thought and became widely known throughout 18th–19th century Europe. The authors conclude that by the breadth of his knowledge, scientific method, and humanistic worldview, Cantemir rightfully stands among the greatest thinkers of his time and represents a truly European personality.